Meningkatkan Kemampuan Motorik Halus Anak Usia 4-5 Tahun Melalui Menjiplak Gambar - Retnoningsih (STAI Syubbanul Wathon Magelang, 2024)
This article aims to explore the potential and techniques for improving fine motor skills in early childhood through tracing images. The research was conducted at TK al-Munawarah located in Pai Village, Wera District, Bima Regency. The subjects of this study were children aged 4-5 years. This study aims to analyze the efforts made by teachers to enhance the students' fine motor skills and to identify the challenges in maximizing the development of these skills at TK al-Munawarah in Pai Village, Wera District, Bima Regency. The results of the study revealed that the efforts to improve the students' fine motor skills were carried out by: (1) preparing image or pattern media in accordance with the lesson theme; (2) explaining the steps for tracing images to the students; (3) establishing indicators for assessing the improvement of children's motor skills. The challenges faced include: (1) insufficient learning tools and media; (2) inadequate and insufficient number of teachers relative to the number of students; (3) insufficient repetition of the material on tracing images, which hindered the optimal development of the children's fine motor skills.